Profitabilitas menjadi pemediasi untuk variabel yang mempengaruhi struktur modal (Studi pada Bank Umum Syariah di Indonesia periode 2016-2020) - Indah Lestari (IAIN Langsa, 2021)
The purpose of this study is to find out and analyze whether there is an Influence of Liquidity, Growth Opportunity, Asset Structure, and Non Debt Tax Shield on Capital Structure with Profitability as an Intervening Variable in Islamic Commercial Banks Registered at OJK 2016-2020